PrEggNut Study: protocol for a randomised controlled trial investigating the effect of a maternal diet rich in eggs and peanuts from <23 weeks' gestation during pregnancy to 4 months' lactation on infant IgE-mediated egg and peanut allergy outcomes. Issue 6 (13th June 2022) - Palmer, Debra J; Sullivan, Thomas R; Campbell, Dianne E; Nanan, Ralph; Gold, Michael S; Hsu, Peter S; Netting, Merryn J; McWilliam, Vicki; Koplin, Jennifer J; Perrett, Kirsten P; Quinn, Patrick; O'Sullivan, Michael; et al.
Abstract : Introduction: Clinical studies supported by immunological data indicate early life intervention strategies to be promising in reducing the growing global burden of food allergies. The events that predispose to food allergy, including the induction of allergen-specific immune responses, appear to be initiated early in development. Early exposure to food allergens in utero and via breast milk is likely to be important in initiating oral tolerance. We aim to determine the effectiveness of higher maternal food allergen consumption during pregnancy and lactation on infant food allergy outcomes. Methods and analysis: This is a multisite, parallel, two-arm (1:1 allocation), single-blinded (outcome assessors, statistical analyst and investigators), randomised controlled trial. Pregnant women (<23 weeks' gestation) whose (unborn) infants have at least two biological family members (mother, father or siblings) with medically diagnosed allergic disease are eligible to participate. After obtaining written informed consent, pregnant women are randomised to either a high egg and peanut diet (at least 6 eggs and 60 peanuts per week) or standard (low) egg and peanut diet (no more than 3 eggs and 30 peanuts per week). The women are asked to follow their allocated diet from <23 weeks' gestation to 4 months' lactation. The primary outcome is food challenge proven IgE-mediated egg and/or peanut allergy in the infants at 12 months of age. Key secondary outcomes include infant sensitisation to egg and/or peanut and infant eczema. Our target sample size is 2136 women. Analyses will be performed on an intention-to-treat basis according to a pre-specified statistical analysis plan. Ethics and dissemination: Ethical approval has been granted from the Women's and Children's Health Network Human Research Ethics Committee (approval number HREC/18/WCHN/42). Trial results will be presented at scientific conferences and published in peer-reviewed journals. Trial registration number: Australian New Zealand Clinical Trials Registry ACTRN12618000937213.